Dominant TP63 missense variants lead to constitutive activation and premature ovarian insufficiency. Issue 10 (29th July 2022) - Tucker, Elena J.; Gutfreund, Niklas; Belaud‐Rotureau, Marc‐Antoine; Gilot, David; Brun, Tiffany; Kline, Brianna L.; Bell, Katrina M.; Domin‐Bernhard, Mathilde; Théard, Camille; Touraine, Philippe; Robevska, Gorjana; van van den Bergen, Jocelyn; et al.
Abstract: Premature ovarian insufficiency (POI) is a leading form of female infertility, characterised by menstrual disturbance and elevated follicle‐stimulating hormone before age 40. It is highly heterogeneous with variants in over 80 genes potentially causative, but the majority of cases having no known cause. One gene implicated in POI pathology is TP63. TP63 encodes multiple p63 isoforms, one of which has been shown to have a role in the surveillance of genetic quality in oocytes. TP63 C‐terminal truncation variants and N‐terminal duplication have been described in association with POI, however, functional validation has been lacking. Here we identify three novel TP63 missense variants in women with nonsyndromic POI, including one in the N‐terminal activation domain, one in the C‐terminal inhibition domain, and one affecting a unique and poorly understood p63 isoform, TA*p63. Via blue‐native page and luciferase reporter assays we demonstrate that two of these variants disrupt p63 dimerization, leading to constitutively active p63 tetramer that significantly increases the transcription of downstream targets. This is the first evidence that TP63 missense variants can cause isolated POI and provides mechanistic insight that TP63 variants cause POI due to constitutive p63 activation and accelerated oocyte loss in the absence of DNA damage.